The Therapeutic Effect of Intravesical Instillation of Platelet Rich Plasma on Recurrent Bacterial Cystitis in Women: A Randomized Clinical Trial - Mirzaei, Mahboubeh; Daneshpajooh, Azar; Farsinezhad, Alireza; Jafarian, Zeinab; Ebadzadeh, Mohammad Reza; Saberi, Narjes; Teimorian, Mohammad (Urology Journal, 2019)
Purpose: Recurrent bacterial cystitis is a common infection in women and there are concerns about its antibiotic therapy. Platelet rich plasma has antimicrobial and tissue repairing effects. We investigated the effect of platelet rich plasma as an intravesical therapy to prevent recurrence of bacterial cystitis. Materials and Methods: Thirty women with a history of recurrent bacterial cystitis were randomly assigned into two groups: 1) platelet rich plasma and 2) control groups. The first group received 10 mL of platelet rich plasma with intravesical instillation plus 40 mL of normal saline. The control group only received 50 mL of normal saline. We did the instillation once a week for four weeks in both groups. We followed up the participants two and 12 months after the last instillation with a questionnaire (the international consultation on incontinence questionnaire in overactive bladder) and result of their urine culture. Results: A significant decrease was observed in the number of bacterial cystitis recurrences in the platelet rich plasma group compared to the control group 12 months after the instillation (4 vs. 1, P = 0.004). Also, there was a significant improvement in the questionnaire’s score two (3.6 ± 2.58 vs. 0.66 ± 1.63, P = 0.002) and 12 months (3.4 ± 2.77 vs. 0.006 ± 1.83, P < 0.001) after instillation in the platelet rich plasma group compared to control group. There was no adverse effect 12 months after instillation. Conclusion: Platelet rich plasma can significantly decrease the recurrence of bacterial cystitis up to a year after instillation without any side effect.